Notch/IL33/ST2 signaling was involved in the maintenance of intestinal epithelial barrier through regulating tight junction after LPS stimulation: Notch/IL33 reduce LPS induced intestinal barrier destruction - Zhang, Yuanling; Xu, Chao; Li, Fang; Chen, Guoqing (Cellular and Molecular Biology, 2025)
Interleukin-33(IL33), an alarm cytokine of the IL-1 family, is expressed mainly in epithelial cells of barrier tissues and is involved in the repair of epithelia to maintain barrier function. However, the mechanisms regulating IL33 expression and the mechanisms by which IL33 regulates the intestinal barrier function are not fully clarified. In this study, Caco-2 cells and siRNA were applied to investigate the role of Notch/IL33/ST2 Signaling in regulating intestinal epithelial barrier function, which was demonstrated by protein expression of tight junctions and trans-epithelial resistance (TER) assay. Our results revealed that Notch signaling pathway was activated and IL33 expression was up-regulated after LPS stimulation. After blocking Notch signaling with DPAT or siRNA for Notch1, IL33 expression was significantly down-regulated in Caco-2 cells. The protein expression of tight junctions (ZO-1, occludin, and claudin-1) was down-regulated after siRNA for IL33 in Caco-2 cells with LPS stimulation. Also, the intestinal epithelial TER was down-regulated after siRNA for IL33 with LPS stimulation or not. Exogeneous IL33 promoted the tight junction protein expression and increased the TER. Finally, our data further showed that IL33 regulates intestinal epithelial barrier function through the ST2 receptor. In conclusion, our results indicated that IL33/ST2 axis, which was activated by the Notch signaling, maintains intestinal epithelial barrier function through regulating tight junction protein expression under inflammatory conditions. This study provides a new therapeutic pathway of regulating intestinal epithelial barrier dysfunction.